The Profile of the Marginal Punk Community and the Driving Factors for Punk - Fajar Munggah Pramdani (The International Journal of Politics and Sociology Research, 2020)
The Punk Community is a group of teenagers who gather together in one container or group that has a lifestyle, trend, fashion, carries the slogan of togetherness (equality,) anti-establishment, anarchism, social solidarity, and anti-oppression in any form whatsoever. Such things are part of the identity that exists in punk children and as slogans punk children are identified through the resistance of punk children or communities against all forms of discrimination, oppression, injustice carried out by the authorities, businessmen, political elites and the government to the community. So by wearing clothes, clothes that tend to be sloppy are a form of punk children's resistance to the authorities. This study uses a qualitative approach, data collection techniques such as, interviews, observations, and observations. By going through the phenomenological approach, the aim is to be able to interview sources or people who have experienced it directly based on their personal experiences and obtain research findings according to events or phenomena that occur, while the subjects in this study were 7 members of the punk community in Lenteng Agung from 10 community members. punk in Lenteng Agung. The selection of the main informants was taken with the characteristics of a random sample, in which a snowball sampling technique aims to obtain information obtained first, so that it starts from one gradually becomes more and more.